A Practical Criterion for the Rapid Detection of Single‐Loop and Double‐Loop Reentry Tachycardias. (25th March 2013) - LINTON, NICK W.F.; WILTON, STEPHEN B.; SCHERR, DANIEL; SHAH, ASHOK J.; DERVAL, NICOLAS; SACHER, FREDERIC; WRIGHT, MATTHEW; HOCINI, MéLèZE; O'NEILL, MARK D.; HAÏSSAGUERRE, MICHEL; JAÏS, PIERRE
Additional Criterion for Entrainment: Introduction: Entrainment criteria for the diagnosis of reentrant atrial tachycardia can be difficult to apply and cannot detect double‐loop reentry. We sought to develop and clinically test a new criterion for the diagnosis of single‐ and double‐loop reentry. Methods and Results: (1) Proposed criterion: after sequential overdrive pacing at 2 different locations and assessing the first ensuing beats of tachycardia, the difference in activation time recorded between 2 appropriate stationary positions changes by 1 or 2 tachycardia cycle lengths; a change of 2 tachycardia cycle lengths usually indicates double‐loop reentry rather than only a single‐loop. (2) Clinical testing: multiple overdrive pacing maneuvers were undertaken and analyzed in 5 patients with common flutter (single‐loop reentry). In total, 23 pairs of overdrive pacing maneuvers were performed using electrodes in the coronary sinus and a distribution of positions in the right atrium. In 22/23 pairs of maneuvers, the change in Activation Difference was within 2.6 ± 12.4 milliseconds of the tachycardia cycle length, confirming single loop reentry. For double‐loop reentry, the literature was reviewed and 3 cases of double‐loop reentry were identified with sufficient data. In all of these cases, double‐loop reentry was detected and also the zone containing the common isthmus was identified. Conclusion: The proposed criterion can diagnose single‐ and double‐loop reentry atrial tachycardia using intracardiac recordings from any pair of well separated positions. The criterion does not require precise electrode placement or extensive activation mapping.